Determination of Nitrogen Rates in Olive (Olea europaea cv Memecik) - Esref Irget, Mehmet; Anaç, Dilek; Ceyhun Kiliç, Cenk; Tepecik, Mahmut; Özer, Kerim (Asian Journal of Chemistry, 2010)
The objective of the present study is to examine the effect of increasing nitrogen rates on yield and nitrogen nutrition of olive trees (cv Memecik). A 5 year nitrogen fertilization experiment was conducted in an olive orchard. Trees were consecutively fertilized at 6 different rates of nitrogen (control-400-800-1200-1600-2000 g N tree-1) in the form of (NH4)2SO4. Yield, leaf total N, NO3-N and NH4-N were measured regularly. Results showed that the trees received 800 g N responded with the highest yield, however, higher rates (1600-2000 g N tree-1) resulted in significant yield depressions. Leaf total N, NO3-N and NH4-N concentrations increased parallel to increasing N rates. Long-term higher rates nitrogen fertilization in the form of ammonium may be the cause of phytotoxicity in olive. Results revealed that for a yield 60-65 kg tree-1 and for optimum nitrogen nutrition, up to 800 g N tree-1 can be applied taken into account the results of initial leaf and soil analysis.